AÇÃO DE REGULADORES VEGETAIS NA PRODUTIVIDADE DO TOMATEIRO - Castro, Paulo R. C.; Oliveira, Maria S.; Demétrio, Clarice G. B. (REVISTA DE AGRICULTURA, 2015)
AÇÃO DE REGULADORES VEGETAIS NA PRODUTIVIDADE DO TOMATEIRO